2022
DOI: 10.26877/eternal.v13i1.10971
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Extensive Reading Principles in an Extensive Reading Class: Students’ Perceptions

Abstract: For running a successful extensive reading (ER) program, Day and Bamford’s ten ER priciples becomes “key ingredients” (Ng, Renandya, and Chong, 2019. P. 172). This study is aimed at revealing EFL students’ perceptions toward the use of the ER principles in their ER class. To achieve the aim, a questionnaire was distributed to 39 students from English Language Education Program, Universitas Kristen Satya Wacana. Besides, an interview to 10 student-respondents was also conducted. The collected data was then anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The influence of RI on the student's basis has previously become research evidence (for example, Judge, 2011). In line with a study from Puspa & Ragawanti (2022), they conducted research by implementing ER principles in an extensive reading class and revealed that the appropriate level of graded readers could lead them to a relaxing atmosphere and promote motivation to read the upper stories of books. The same findings can be found in Gopal et al (2022), who examined the utilization of ER from the perspective of ESL students ' reader responses.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The influence of RI on the student's basis has previously become research evidence (for example, Judge, 2011). In line with a study from Puspa & Ragawanti (2022), they conducted research by implementing ER principles in an extensive reading class and revealed that the appropriate level of graded readers could lead them to a relaxing atmosphere and promote motivation to read the upper stories of books. The same findings can be found in Gopal et al (2022), who examined the utilization of ER from the perspective of ESL students ' reader responses.…”
Section: Discussionmentioning
confidence: 97%
“…The finding also supports previous studies confirming sustainable vocabulary acquisition development resulting from intensified reading activities. Several studies have strengthened the evidence of extensive reading engagement to contribute to several aspects of second language learning, such as reading comprehension and reading rates (Belgar & Hun, 2014), and vocabulary and spelling (Pigada & Schmit 2006;Liu & Zhang, 2018;Sun, 2020;Ateek, 2021;Puspa & Ragawanti, 2022). Other experts, such as (Renandya, 2016), have exaggerated extensive reading to have attracted increasing attention from second language and foreign language researchers and educators over recent decades.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, rigorous reading activities contributed to the improvement of knowledge and English abilities, including writing, speaking, listening, reading, vocabulary, and grammar. It is added Sartika (2020) that students provided positive feedback regarding the ER platform, and their English proficiency improved in some areas.…”
Section: A Benefits Of Extensive Reading (Er)mentioning
confidence: 99%
“…The extensive reading strategy, which contains ten principles from Day and Bamford, is very suitable to be implemented to help with motivational problems in reading (Ng et al, 2019). In addition, the ten principles of extensive reading from Day & Bamford are also able to improve students' abilities, especially in the field of language; this increase is not only in the linguistics aspect but also non-linguistics (Puspa & Ragawanti, 2022).…”
Section: Introductionmentioning
confidence: 99%